Scenario of climate change and livestock - Patel, N R; Chaudhary, A P (Indian Journal of Animal Production and Management, 2018)
Climate change means change in one or more components of climate over a very long period which causes changes in land and ocean temperature, spatial and temporal precipitation pattern, sea level, sea, ice, vegetation, season and increases in the frequency and intensity of weather events. These changes affect livestock directly or indirectly. Direct effect includes growth, milk production, reproduction of livestock, change in different physiological parameters related to adaptation and increase in vector borne diseases. Different causative agents of emerging and re-emerging diseases increase or decrease in population according to climate. Indirect effects include reduction and/or non-availability of feed and water resources. Reductions of feed and water resources means qualitative and quantitative availability of feed and water so there is need to form different strategies to reduce climate change. It involves both human and livestock